Efficacy and safety of cadonilimab (PD-1/CTLA-4 bi-specific antibody) and adjuvant anti-angiogenesis therapy in treated, recurrent, or metastatic cervical cancer - Zhou, Fang; Liu, Shushu; Zuo, Ying; Naseem, Danial F.; Li, Yinguang; Wang, Yin; Meng, Cuicui; Song, Yipeng (Frontiers in Oncology, 2025)
BackgroundCombined immunotherapy and antiangiogenic therapy have exhibited synergistic antitumor effects in several cancers. The prognosis of recurrent or metastatic cervical cancer (r/mCC) is poor, especially for patients with prior multi-line treatments. This study aimed to evaluate the efficacy and safety of cadonilimab(PD-1/CTLA-4 bispecific)with anti-angiogenesis adjuvant therapy (bevacizumab or anlotinib) in pretreated patients with r/mCC.MethodsNineteen patients treated with cadonilimab plus bevacizumab or anlotinib with or without chemotherapy were included. Cadonilimab was administered at dose of 10mg/kg intravenously. Patients receiving anti-angiogenic therapy received either bevacizumab or anlotinib administered orally. The safety, objective response rate (ORR), progression-free survival (PFS) and overall survival (OS) were assessed.ResultsThe median follow-up was 15.5 months study patients. Among all 19 patients, 2 patients (10.5%) achieved complete response (CR), 2 patients (10.5%) achieved partial response (PR) and 4 patients (21.1%) achieved stable disease (SD), with an ORR of 21.1% and DCR of 42.1%. Moreover, the median PFS was 10.5 months (95% CI: 6.1-14.9 months) and 1-year OS rate was 78.3%. Proteinuria (47.4%) and hypertension (42.2%) were the most common treatment-related adverse events (TRAE), with 5 (26.3%) patients experiencing Grade 3 TRAEs, while no treatment related deaths were observed.ConclusionsThis is the first report exploring the efficacy and safety of treating patients concurrently with Cadonilimab plus bevacizumab or anlotinib with heavily pretreated r/mCC. The findings suggest that this regimen might be potentially efficacious and safe with relatively manageable toxicity. Further trials with a control arm are required to validate our findings.